Micro-Housing as an Alternative Solution Housing Solution to the Big City - Hashim, Nur-Iman; Aminuddin, A M R (MAJ - Malaysia Architectural Journal, 2022)
Malaysia’s federal capital, Kuala Lumpur, is the country’s most populated and biggest metropolis. The city, on the other hand, becomes a ghost town at night, when the city’s working population retires to the suburbs. Micro-housing may be an option for addressing this problem. This research tries to identify how micro-housing may be implemented in Kuala Lumpur by looking at micro-housing antecedents in places like New York and Seoul, as well as interviewing the design team behind the Kuala Lumpur micro-housing design concept "Micro-Village."